EFEKTIVITAS PENGGUNAAN JARING KABUT DALAM KOLEKSI CHIROPTERA (MEGACHIROPTERA DAN MICROCHIROPTERA) - jason Thomas Karuntu; Annawaty (Biocelebes, 2020)
The use of traps is very important in the process of sampling bats in the field. The mist net is a type of traps that commonly used to catch bats for research purposes. This study aims to determine the effectiveness of using mist nets in bats sampling. Sampling site located in the Lindu Plain, District of Sigi, Central Sulawesi. Bats were sampled by mist nets using purposive sampling method, at four different types of habitat. The result of this study indicated that mist net is effective in catching fruit-eating bats (Megachiroptera), but is not effective in capturing insectivorous bats (Microchiroptera).